Interactive effect of FYM and mulching on productivity and water use efficiency of squash melon (Citrullus vulgaris var. fistulosus) grown with supplemental irrigation in hot arid region of Rajasthan - BIRBAL, BIRBAL; SONI, M L; RATHORE, V S; NATHAWAT, N S; RENJITH, P S (The Indian Journal of Agricultural Sciences, 2019)
Squash melon (Citrullus vulgaris var. fistulosus Steward) is a rainfed crop in arid region but in these areas, the rainy days are very less. Due to this reason, the farmers could not get desired yield. Hence supplemental irrigation with water conservation practices is required for getting the economic return from this crop. Hence an experiment was conducted at ICAR-Central Arid Zone Research Institute, Regional Research Station, Bikaner, Rajasthan to study the effect of three mulching treatments (No mulching, straw mulching (2.5 tonnes/ha) using local shrub Leptadenia pyrotechnica and black polyethylene plastic mulching of 25 micron thickness) and four FYM doses (0, 20, 30 and 40 tonnes/ha) on growth, yield, WUE and economics of Squash melon grown with supplemental irrigation during kharif seasons of 2012 and 2013. Vine length, numbers of fruits per plant and yield of squash melon were significantly influenced by FYM, mulching and their interaction during both the years of experiment. Application of FYM caused significant improvement in squash melon yield up to 30 tonnes/ha. Averaged across mulching treatments, application of FYM @ 20, 30 and 40 tonnes/ha resulted 47.8, 79.5 and 88.4% higher yields compared to control. Application of mulch brought significant improvement in yield and yield components and the response of mulch varied with the level of FYM application. Plastic and straw mulching resulted 26.6 and 48.6% higher yield over no-mulch treatment. Straw mulch recorded the longest vine length, the highest numbers of fruits per plant and yield. The highest yield was recorded with application of 30 tonnes FYM /ha combined with straw mulch.